European societies : fusion or fission? - Boje, Thomas P., 1944-; Steenbergen, Bart van; Walby, Sylvia (Routledge/European Sociological Association studies in European societies, 1999)
This book brings together many of the leading experts in the field to ask whether recent developments in Europe have brought about a higher level of integration or are causing increased divergence and differences between countries.